Using ARIAS Model to Improve Students’ Speaking Ability at SMP Negeri 9 Parepare - Nanning, Nanning; Putri, Nabilah Lathifah; Kalsum, Kalsum (STAIN Majene, 2023)
ARIAS learning model consists of assurance, relevance, interest, assessment, satisfaction which is arranged based on learning theories. The five components are one unity that requires learning process to be more effective to improve students’ confidence in speaking. Many students’ still afraid to speak and did not have any self confidence in speaking. The purpose of this research is to know whether or not ARIAS Model can improve students speaking ability at SMP Negeri 9 Parepare. This research used experiment design with pre-experimental design, the total samples were 29 students. To gain the data, this research employed pre-test and post-test as instruments. The data were analyzed by using SPSS. The result of the research showed that there was improvement of students speaking ability at SMP Negeri 9 Parepare after having taught by ARIAS Model. The students speaking skill before learning by using of ARIAS Model was 64,33. After having treatment by using of ARIAS Model, students’ speaking ability increased by 80.52. The improvement obtained t value 2.507 > 2.011, which means that there was a significant improvement students speaking ability using ARIAS Model at SMP Negeri 9 Parepare.